STUDI KOMPARASI SNI 01-4449-2006 DENGAN JIS A 5905 : 2003 . - Ulfah Hanum Nasution; Yunus Afifuddin; Lutfhi Hakim (Program studi Kehutanan USU, 2015)
Japan and Indonesia has own criteria in determinating the applicable standards for fiberboard in accordance with the development of industry in each country. JIS and SNI have differences and similarities that are only applicable in their respective countries so that the necessary information to evaluate these standards in order to be valid not only in each country. The purpose of this research is to compare SNI 01-4449-2006 with JIS A 5905-2003. Data analysis was done by using descriptive comparative technic that is compare standards specified in SNI 01-4449-2006 with JIS A 5905-2003 so that known differences and similarities of each standard. Result of the comparition between the parameter of JIS A 5905-2003 and SNI 01-4449-2006 show that the overall standard is different. The difference between these two standardsis available on the parameters of normative parameters of mold thickness, length and width, provided that te testing and measurement of test samples. JIS A 5905-2003has testing standards for fire resistance test and resistance for weather and SNI 01-4449-2006 doesn’t have that testing standards. Based of the comparition of the parameters between JIS A 5905-2003 and SNI 01-4449-2006, it can be concluded that JIS A 5905-2003is more complete than SNI 01-4449-2006.Keywords: Indonesia National Standard, Japanese Industrial Standar, Compare.